Common surgical practice in the treatment of patients with popliteal artery aneurysm among vascular centers in Serbia - Zarić, Aleksandar; Tomić, Aleksandar; Marjanović, Ivan; Manojlović, Vladimir; Budakov, Nebojša; Ilić, Anica; Vujčić, Aleksandra; Nešković, Mihajlo; Atanasijević, Igor; Stepanović, Nemanja; Stanković, Jelena; Jovanović, Milan; et al. (Vojnosanitetski pregled, 2023)
Background/Aim. Popliteal artery aneurysm (PAA) is the most common peripheral artery aneurysm and the second most common aneurysm following abdominal aortic aneurysm (AAA). Still, its incidence is rare, and treatment is non-standardized. The collection of data in a multicenter registry could improve the diagnosis and treatment of PAA. SerbVasc is a newly established data collection collaboration among vascular centers in Serbia. The aim of this study was to present common surgical practices in the diagnosis and treatment of patients with PAA in hospitals in Serbia. Methods. Vascular centers in Serbia that accepted the invitation collected data retrospectively concerning patients operated on for PAA from 2012 to 2018. Data regarding symptoms, preoperative diagnostics, vascular and endovascular techniques, and postoperative results were collected. This data set was submitted to the VASCUNET international project of PAA for data analysis between the countries. The same data set was used for a detailed analysis of the contemporary treatment of PAA in six hospitals in Serbia: University Clinical Center of Serbia, “Dedinje” Cardiovascular Institute, Military Medical Academy, University Clinical Center Novi Sad, University Clinical Center Niš, and General Hospital Užice. Results. From 2012 to 2018, in six hospitals in Serbia, data for 342 procedures on treating PAA were collected for 329 (96.2%) men and only 13 (3.8%) women. The incidence of PAA repair was 6.8 operations per million inhabitants a year. The mean age of patients was 64.34 years (ranging from 29 to 87). A total of 223 (65.8%) elective procedures were performed. Amputation and hospital survival were considered the main outcomes. Thrombosis was recorded in 110 (32.5%) patients as a cause for surgery, and rupture was recorded in 5 patients. The mean diameter of the aneurysm was 35.3 mm, and a slightly larger diameter was recorded in ruptured aneurysms – 43.8 mm on average. Both synthetic and vein grafts were used in elective and urgent procedures equally. Endovascular procedures were performed in 6 (1.8%) cases. Conclusion. This study confirms the importance of registry-based collection of data and their analysis. It showed that the national incidence of PAA in Serbia is low and that well-organized, even institution-based, screening algorithms should improve identifying such patients and increase the number of electively treated PAA. Educating vascular surgeons to use the posterior approach could improve vascular healthcare.
Keywords: endovascular procedures; popliteal artery aneurysm; serbia; vascular surgical procedures